Global research hotspots and trends in halal research: a scientometric review based on descriptive and CiteSpace analyses - Mohd Zaki, Nor Nadiha; Lani, Mohd Nizam; Azra, Mohamad Nor; Mohd Noor, Mohd Iqbal; Alias, Rozila; Mahyudin, Nor Ainy; Mohd Hashim, Amalia; Mohd Desa, Mohd Nasir (Akademia Baru Publishing, 2023)
The halal industry is growing, and there is an increasing recognition of its importance among academics, practitioners, and other industry stakeholders. However, there is limited scientometric research using CiteSpace analysis on halal research. This study is the first to report on scientometric research that used CiteSpace analysis to identify the extent of halal publications. The Web of Science Core Collection databases were queried, and CiteSpace was used for co-citation analysis, while Microsoft Excel was used for descriptive analysis. Our analysis included 1139 publications available in WOSCC between 1987 and 2021. We found a fifteen-fold increase in halal-related publications between 2010 (10) and 2021 (150). Malaysia (37%) and Indonesia (15%) were the top two countries with combined publications more than 50% of published papers. Our literature co-citation cluster analysis identified eleven clusters, with the most prominent being halal tourism, halal certification, pig adulteration, and halal logistics. The major fields with the highest number of halal-related publications were: (i) “Veterinary, Animal Science”, (ii) “Psychology, Education, Health”; and (iii) “Economics, Economic, Political”. Scientometric analysis of halal research can identify the focal points and frontiers of the field. This study offers valuable theoretical and real-world references, recent developments, and opportunities for collaboration.